Analisis Pengaruh Belanja Modal, Belanja Pendidikan, Kredit, Investasi, dan UMP Terhadap Produktivitas Tenaga Kerja Sektor Pertanian - Mubarak, Ahmad Samhan; Rukmana, Didi; Rahmatiah, Rahmatiah; Yunus, Amanus Khalifa Filardi (Universitas Galuh, 2024)
Agricultural sector still become pedestal absorption of the highest labor compared with others, however with the highest absorption labor in the sector agriculture is comparable with productivity its labor. This research purpose to analyze and measure in amount of capital expenditure influences, education expenditure, credit, investment and UMP to labor productivity in South Sulawesi and West Sulawesi. The secondary data form of panel is used in this research by combine 2010 -2021 time series and a cross section of 2 provinces on the island of Sulawesi namely the provinces of South Sulawesi and West Sulawesi in the form reports are collected from Bank Indonesia, Central Bureau of Statistics, Ministry of Finance Directorate general Balance Finance. The research results show that the determining factors for labor productivity in the agricultural sector in South Sulawesi Province are investment variables and UMP, while in West Sulawesi province it is capital expenditure.